Secular trends of dental caries and association with nutritional status: a retrospective analysis of 16,199 Chinese students from three successive national surveys from 2010 to 2019 - Hao, Changfu; Hao, Yudan; Lou, Xiaomin; Wang, Xiaolin; Liu, Weiping; Zhou, Huijun; Ban, Xiaolei; Wu, Wencan; Wang, Xuejie; Wang, Xian (Frontiers in Public Health, 2024)
The prevalence of dental caries (DC) among students in developing countries has increased at an alarming rate and nutritional status has been shown to be associated with DC in children and adolescents with inconsistent conclusions. We aimed to understand the trends of DC prevalence in students aged 7, 9, 12, 14 and to explore the relationship between DC prevalence and nutritional status.We recruited 16199 students aged 7, 9, 12, 14 in China by multi-stage, stratified, random sampling methods in 2010 to 2019. Permanent caries were measured using the Decay, Loss, and Filling (DMF) index and prevalence rate. Deciduous caries were measured using the decay, loss, and filling (dmf) index and prevalence rate. Nutrition status was assessed by body mass index (BMI) and hemoglobin levels. Logistic regression analysis was used to assess the association between nutrition status and the DC prevalence in children and adolescents with information concerning family-related factors.Results: Results indicated that DC prevalence increased from 39.75% in 2010 to 53.21% in 2019 in Henan province, with deciduous teeth and permanent teeth being 45.96% and 27.18% respectively in 2019. Total caries rate decreased with age and caries rate of girls was higher than that of boys in 2019 (55.75% V.S.50.67%). The prevalence of dental caries among primary and secondary school students in areas with medium economic aggregate was the highest, followed by cities with the best economic development level, and cities with low economic level have a lower prevalence of dental caries. Dental caries was negatively correlated with body mass index. In the fully adjusted model, underweight children had a higher caries prevalence (OR=1.10, 95%CI: 0.86-1.41). Children with anemia had a higher prevalence of dental caries (OR=1.18, 95%CI: 0.98-1.42).The DC prevalence of students in Henan Province was high, with a tendency to increase.Females, young individuals, and those with a higher economic level showed a positive correlation with the prevalence of caries. In the process of economic development, particular attention should be paid to early childhood caries prevention. Nutritional status should be taken seriously among children and adolescents and oral health system should be improved to keep pace with economic development.